2000
DOI: 10.1016/s1074-7613(00)00026-1
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Established Tumors by CD8+ T Cell Adoptive Immunotherapy

Abstract: We generated the DUC18 T cell receptor transgenic mouse expressing an H-2Kd -restricted transgenic T cell receptor specific for the syngeneic CMS5 fibrosarcoma rejection antigen mutated ERK2(136-144). DUC18 mice were capable of specifically eliminating lethal CMS5 tumor challenges, and transfer of DUC18 splenocytes to naive nontransgenic recipients conferred protection from subsequent and established CMS5 tumor burdens. Eradication of established tumor burdens by adoptive transfer of DUC18 splenocytes was dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
285
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(303 citation statements)
references
References 43 publications
12
285
0
4
Order By: Relevance
“…Investigations of transgenic mice with deficient responses to interferon-γ (IFN-γ), a cytokine that has been shown to be required for migration of T cells to tumour sites 58,59 , have led to increased interest in the mechanisms by which immune cells target tumours 60,61 . Although T cells seem to be the main effectors of immune surveillance 62 , the innate immune system (which includes natural killer cells, macrophages, monocytes and mast cells) is also involved [63][64][65] .…”
Section: Immune Function In the Tumour Contextmentioning
confidence: 99%
“…Investigations of transgenic mice with deficient responses to interferon-γ (IFN-γ), a cytokine that has been shown to be required for migration of T cells to tumour sites 58,59 , have led to increased interest in the mechanisms by which immune cells target tumours 60,61 . Although T cells seem to be the main effectors of immune surveillance 62 , the innate immune system (which includes natural killer cells, macrophages, monocytes and mast cells) is also involved [63][64][65] .…”
Section: Immune Function In the Tumour Contextmentioning
confidence: 99%
“…Starting with the pioneering work of Rammensee and colleagues [5,9], Kd has been widely studied, and Kd-specific immune responses described in a number of experimental systems. These include CD8 T cell responses: (1) against viral and bacterial pathogens [6,[19][20][21][22]; (2) in the NOD mouse model of diabetic autoimmunity [23][24][25][26][27]; and, (3), to tumor antigens [28][29][30][31]. Despite these many studies, the number of identified endogenously processed peptides selected by Kd is small.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively slow induction of anti-HER2 immunoresponses after DNA vaccination may make the suppression of continuously growing tumors extremely difficult in the setting of these animal models. 30 Since one of the attractive characteristics of DNA vaccination is the long-lasting specific immune response to cognate antigens, DNA vaccination could be an attractive approach for preventing recurrence and metastasis of cancer, both of which often occur even after long latent periods. When the effect of DNA vaccination was investigated in pulmonary metastasis models of HER2-expressing tumors, we noted significant suppression of metastasis when immunization was initiated on the day of intravenous tumor challenge or 3 days after the tumor challenge.…”
Section: Discussionmentioning
confidence: 99%